Epigenetically-Regulated MicroRNA-9-5p Suppresses the Activation of Hepatic Stellate Cells via TGFBR1 and TGFBR2 - Fujun Yu; BiCheng Chen; XuFei Fan; Guojun Li; Peihong Dong; Jianjian Zheng (Cellular Physiology and Biochemistry, 2017)
Background/Aims: Recently, microRNAs (miRNAs) have been demonstrated to act as regulators of activation of hepatic stellate cells (HSCs). It is well known that the main profibrogenic inducer transforming growth factor-β1 (TGF-β1) contributes to HSC activation, which is a key event in liver fibrosis. Increasing studies show that miR-9-5p is down-regulated in liver fibrosis and restoration of miR-9-5p limits HSC activation. However, the role of miR-9-5p in TGF-β1-induced HSC activation is still not clear. Methods: miR-9-5p expression was quantified using real-time PCR in chronic hepatitis B (CHB) patients and TGF-β1-treated LX-2 cells. In CHB patients, histological activity index (HAI) and fibrosis stages were assessed using the Ishak scoring system. Effects of miR-9-5p on liver fibrosis in vivo and in vitro were analyzed. Luciferase activity assays were performed to examine the binding of miR-9-5p to the 3′-untranslated region of type I TGF-β receptor (TGFBR1) as well as TGFBR2. Results: Compared with healthy controls, miR-9-5p was reduced in CHB patients. There was a lower miR-9-5p expression in CHB patients with higher fibrosis scores or HAI scores. miR-9-5p was down-regulated by TGF-β1 in a dose-dependent manner. TGF-β1-induced HSC activation including cell proliferation, α-SMA and collagen expression was blocked down by miR-9-5p. Notably, miR-9-5p ameliorates carbon tetrachloride-induced liver fibrosis. As determined by luciferase activity assays, TGFBR1 and TGFBR2 were targets of miR-9-5p. Further studies demonstrated that miR-9-5p inhibited TGF-β1/Smads pathway via TGFBR1 and TGFBR2. Interestingly, promoter methylation was responsible for miR-9-5p down-regulation in liver fibrosis. The relationship between miR-9-5p expression and methylation was confirmed in CHB patients and TGF-β1-treated cells. Conclusion: Our results demonstrate that miR-9-5p could inhibit TGF-β1-induced HSC activation through TGFBR1 and TGFBR2. Loss of miR-9-5p is associated with its methylation status in liver fibrosis.